HOW TO MAKE AN ILL-STUCTURED PROBLEM TO BE WELL DONE? : A STUDY ABOUT DECISION MAKING OF PRE SERVICE MATH TEACHER IN COMPLETING THE STRUCTURE - Suwarno, Suwarno (Universitas Negeri Malang, 2019)
Ill-Structured Problem has authenticity, complexity, and openness properties, so that the characteristic of Ill-Structured Problem is unique, especially in incompletely of structure. The qualitative study was held to describe the decision making in completing the structured of Ill Structured problem. The research subjects are 3 out of 22 prospective Mathematics teachers who perform decision making in achieving Ill Structured Problem. The research found that each item shows a different response in the decision-making stage that involves generating, clarifying, and assessing reasonableness idea depend on knowledge, experience in their daily life.